PARTISIPASI MASYARAKAT DALAM BUMDES DI DESA BULAWAN II KECAMATAN KOTABUNAN KABUPATEN BOLAANG MONGONDOW TIMUR (Community Participation in the Village-Owned Enterprise (BUMDes) in the Village of Bulawan II, Kotabunan District of East Bolaang Mongondow Regency) - Haikal Mokoagow; Audrey M. Maweikere; Martha M. Sendow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The purpose of this study was to determine the level of communityÂ  participation in the Village-Owned Enterprise (BUMDes) of Bulawan II Village, Kotabunan sub-district, East Bolaang Mongondow Regency. This research was conducted for three months, from May to July 2019.The results showed that only 20% had participated, while 80% did not participate in the BUMDes program in laying hens in Bulawan II Village, Kotabunan District, Bolaang Mongondow Timur Regency. This showed that the level of community participation in BUMDes was still relatively low. One of the reasons was the lack of information or notification to the public to attend meetings held by the BUMDes management.Keywords: Village-owned Enterprise, community participation, BUMDes